Serum transforming growth factor-beta levels and severity of retinoblastoma in children - M Farid Huzein; Nadirah Rasyid Ridha; Dasril Daud (Indonesian Pediatric Society, 2023)
Background Transforming growth factor-? (TGF-?) expression contributes to the growth of retinoblastoma. TGF-? is produced or released by infiltrating cells such as lymphocytes and monocytes/macrophages. TGF-? levels are a potential marker of disease severity. Objective To assess the difference in serum TGF-? levels before chemotherapy in patients with retinoblastoma grades III and IV. Methods This cross-sectional observational study was done at Dr. Wahidin Sudirohusodo Hospital, Makassar, Indonesia from January to November 2019. Subjects were pediatric patients with grade III and IV retinoblastoma who had not undergone chemotherapy. Patients who met the inclusion criteria provided blood specimens for TGF-? testing. We analyzed the difference in serum TGF-? level between grade III and grade IV patients. Results We obtained 38 subjects, consisting of 13 grade III and 25 grade IV retinoblastoma patients. Mean TGF-? levels were in 1,061 ng/L in grade III and 988 ng/L in grade IV patients. The Mann-Whitney U test revealed no significant difference between the levels of TGF-?, retinoblastoma grade III and IV (P=0.655). However, TGF-? levels in both groups were markedly above the normal value (100 ng/L). Conclusion TGF-? levels are markedly increased in grade III and IV retinoblastoma patients. There was no significant difference in TGF-? level between grade III and IV patients. Our findings suggest that TGF-? plays an important role in tumor cell development. Further research on differences in TGF-? levels between late stages (grades III and IV) and early stages (grades I and II) of retinoblastoma to elucidate the role of TGF-? as a marker of retinoblastoma severity.